Additional file 3 of Phylogenetic analysis of the caspase family in bivalves: implications for programmed cell death, immune response and development - Susanne Vogeler (3428648); Stefano Carboni (2339416); Xiaoxu Li (12771); Alyssa Joyce (721836) (2021)
Additional file 3: Phylogenetic relationship of the gasdermin family of Crassostrea gigas (CgGSDM1: XP_034300415; CgGSDM2: XP_034300423) and other invertebrates and vertebrates.